Gaelic Scotland in the Colonial Imagination Anglophone Writing from 1600 to 1900 - Stroh, Silke (Northwestern University Press, 2016)
Can Scotland be considered an English colony? Is its experience and literature comparable to that of overseas postcolonial countries? Or are such comparisons no more than victimology to mask Scottish complicity in the British Empire and justify nationalism? These questions have been heatedly debated in the aftermath of the 2014 referendum on independence and amid a continuing campaign for more autonomy. Gaelic Scotland in the Colonial Imagination offers an introduction to the emerging field of postcolonial Scottish studies, assessing both its potential and limitations to promote further interdisciplinary dialogue. Accessible to readers from various backgrounds, the book combines overviews of theoretical, social, and cultural contexts with detailed case studies of literary and nonliterary texts. Silke Stroh shows how the image of Scotland's Gaelic margins changed under the influence of the emergence of the modern nation-state and the rise of overseas colonialism.